International financial statistics /Sept. 2003 - International Monetary Fund; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Publishes for most countries of the world, currentdata on exchange rates, international liquidity, international banking, money and banking, interest rates, prices, production, international transactions (including balance of payments and international investment position), government finance and national accounts.
Sept. 2003
eej 4/3/2020
Ref.
Keywords: Finance; International finance